Penyuluhan Dan Pelatihan Optimalisasi Matematika Terhadap Penguatan Ekonomi di Era Pandemi untuk Siswa SMA Muhammadiyah 2 Palangkaraya - Rospala Hanisah Yukti Sari; Istighfaris Rezki; Reza Zulfikar Akbar (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
Mathematics as a subject that is oriented towards implementation in daily life. Mathematics is the basic science of other sciences, so it is interrelated with other sciences. Mathematics can be developed in other science, including economics and engineering. Therefore, concepts in mathematics need to be introduced to students. Thus, it is hoped that the introduction and training of mathematics that implemented in economics and engineering can help students in efforts to strengthen the economy, especially in the current pandemic era